Disordered sleep in elite athletes - possible solutions - McCloughan, L.; Anderson, R. (InPsych, 2014)
About the importance of sleep and sleeping disorders in athletes (causes, effects) and possible solutions. Conclusion: Given the banned use or restriction of many sedatives for professional athletes, there is a need to continue to promote alternative strategies that facilitate sleep both in and out of competition to provide effective alternatives to the use of medication. In addition, athletes need to be encouraged to engage in psychological services to assist in the management of anxiety and learn to effectively cope with the stress of the competition environment. Finally, multidisciplinary collaboration with medical staff to provide a holistic response to the issue is of great benefit to the athlete.